String-powered microfluidic chip integrating heparin-mediated one-pot RT-RPA/CRISPR-Cas12a for multiplex detection of HFMD viruses - Chen, Zhen; Mao, Kang; Meng, Hanqing; Gao, Chen; Lv, Haoran; Li, Xiqing; Zheng, Qiuda; Yang, Zhugen; Hamza, Ibrahim Ahmed; Tu, Chenglong; Zhang, Hua (American Chemical Society (ACS), 2026)
Hand, foot, and mouth disease (HFMD) is a common childhood infection caused by enteroviruses, which exhibit distinct regional and seasonal epidemiological patterns. Wastewater-based epidemiology is a crucial tool for monitoring population infection dynamics and viral subtype distribution. However, the lack of effective on-site viral detection methods limits timely early warning and effective surveillance of infectious disease outbreaks. This study developed a one-pot RT-RPA/CRISPR-Cas12a assay-based, string-powered flywheel microfluidic chip for the multiplex detection of HFMD viruses in wastewater. First, by leveraging the regulatory effect of heparin sodium on CRISPR/Cas12a activity, a one-pot RT-RPA/CRISPR-Cas12a system was constructed to detect four major subtypes of HFMD virus (EV-A71, CV-A16, CV-A6, and CV-A10). Subsequently, this method was integrated into a pull-wire, flywheel-type, dual-axis centrifugal microfluidic chip, named the Heparin-Inhibited CRISPR-Associated System Chip (HICAS-Chip), enabling integrated enrichment, purification, elution, and multiplexed detection. The HICAS-Chip allowed visual detection of nucleic acids at 10 aM sensitivity within 1 h, corresponding to the sensitivity of the one-pot RT-RPA/CRISPR-Cas12a assay. During a year-long wastewater monitoring program in Guiyang City, China, the HICAS-Chip identified EV-A71 and CV-A10 as the predominant circulating subtypes, with incidence peaks observed in June, November, and December. The wastewater detection results obtained using HICAS-Chip showed high concordance (95.83%) with RT-qPCR assays. This platform provides an efficient portable device for the early detection and continuous monitoring of HFMD epidemic trends by wastewater-based epidemiology.
Keywords: 3207 Medical Microbiology; 32 Biomedical and Clinical Sciences; Bioengineering; Emerging Infectious Diseases; Infectious Diseases; Prevention; 4.1 Discovery and preclinical testing of markers and technologies; Infection; 3 Good Health and Well Being; Analytical Chemistry; 3205 Medical biochemistry and metabolomics; 4004 Chemical engineering; Hand, foot and mouth disease; Heparin sodium; Microfluidics; One-pot CRISPR/Cas12a; Wastewater-based epidemiology; CRISPR-Cas Systems; Hand, Foot and Mouth Disease; Heparin; Humans; Lab-On-A-Chip Devices; Wastewater; Nucleic Acid Amplification Techniques